Sams teach yourself Adobe Photoshop CS2 in 24 hours - Rose, Carla (SAMS, 2005)
Create works of art using your computer, Adobe Photoshop CS 2 and Sams Teach Yourself Photoshop CS 2 in 24 Hours . Learn the basics of Photoshop with a minimum of jargon from market-leading author, Carla Rose . Her conversational, friendly approach will make Photoshop seem less intimidating and more manageable to learn. With Carla's help, you will learn to: Select color modes Use paintbrushes and art tools Use layers, masks and paths Use artistic filters Apply special effects to pictures Enhance and repair photos Master the world's leading image editing and manipulation tool with this accessible yet detailed, step-by-step tutorial.